2008
DOI: 10.1159/000173741
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Mutations in Greek Sotos Patients with Rare Clinical Manifestations

Abstract: Background: Sotos syndrome is an autosomal dominant disease characterized by tall stature, advanced bone age, typical morphological abnormalities of the face and developmental delay. It is caused by mutations in the NSD1 gene located on chromosome 5. NSD1 mutations are detected in the majority of the Sotos patients, and include intragenic NSD1 mutations and microdeletions in the 5q35 region. Cardiovascular and urogenital symptoms are more frequent in the microdeletion group. Methods: Mutation analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
1
8
0
1
Order By: Relevance
“…Advanced bone age was found in 76% of individuals. The authors concluded that overgrowth is not obligatory for the diagnosis of Sotos syndrome and advanced bone age should not be considered as mandatory diagnostic criterion, in agreement with other authors (Leventopoulos et al 2009a). However, classic phenotype of Sotos syndrome is conventionally considered as one of the most frequent overgrowth conditions, although its variable expressivity has been clearly noted.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Advanced bone age was found in 76% of individuals. The authors concluded that overgrowth is not obligatory for the diagnosis of Sotos syndrome and advanced bone age should not be considered as mandatory diagnostic criterion, in agreement with other authors (Leventopoulos et al 2009a). However, classic phenotype of Sotos syndrome is conventionally considered as one of the most frequent overgrowth conditions, although its variable expressivity has been clearly noted.…”
Section: Introductionsupporting
confidence: 86%
“…Developmental delay is characterized by clumsiness, some degree of learning impairment; adaptive problems, autistic features, attention deficit and hyperactivity disorders could be present. Most affected individuals show no specific neuroimaging abnormalities: ventricular dilatation and hypoplasia of the corpus callosum are commonly reported (Leventopoulos et al 2009a). Finally, Sotos syndrome is associated with an increased risk of benign or malignant tumours, recently estimated about 2%-3%.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics which typify Sotos syndrome include advanced skeletal maturation as a consequence of accelerated overgrowth particularly in early infancy [Wit et al, ]; long narrow face, high forehead, frontal bossing, high arched palates, prominent jaws, and an unusually large head [Cole and Hughes, , ]; large hands and feet from birth [Hook and Reynolds, ] and intellectual disability of varying degrees [Tatton‐Brown et al, ]. Delayed motor skill development has been reported across a majority of studies, with younger children displaying early psychomotor delay [e.g., Bloom et al, ; Leventopoulos et al, ] and clumsiness reported in older children [e.g., Bale et al, ; Trad et al, ]. Improvement has been observed during adolescence [Mauceri et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of mutations of the large NSD1 gene are causative of the syndrome (Kurotaki et al, 2001(Kurotaki et al, , 2002. Several hundred intragenic point mutations as well as exonic deletions and microdeletions covering the large NSD1 gene have been described in the patients, and no mutational hotspot has been detected (Faravelli, 2005;Leventopoulos et al, 2009). Most cases are sporadic, but in a few families, autosomal dominant inheritance has been reported (Hö glund et al, 2003;TattonBrown et al, 2005).…”
Section: Introductionmentioning
confidence: 99%